RADIO ACCESS TECHNOLOGIES IN 5G COMMUNICATION NETWORKS - Urquiza Villalonga, David Alejandro (Telemática, 2020)
The fifth-generation (5G) network has been designed to support highly reliable and fast communication technologies to satisfy the increasing demands for higher values of data rates, device density, user mobility, spectrum, and energy efficiency [1]. In these networks, a service-oriented architecture is developed to support a wide range of emerging applications and services with a demanding requirement of quality of user experience (QoE). 5G systems are designed as flexible, customizable, scalable and deployable networks where new paradigms as network function virtualization (NFV), software-defined networking (SDN), artificial intelligence (AI) and network slicing have emerged [2]. Besides, new radio access network (RAN) schemes have been developed by several standard development organizations (SDO) to meet the demanding key performance indicators (KPIs) of 5G communication systems. This technically speaking is addressed to illustrate the new use-cases in 5G networks and the required KPIs to achieve these emerging applications. Main insights regarding the RAN technologies are also described focusing on millimeter wave (mmWave) communication, massive multiple inputs multiple outputs (mMIMO), small cells (SCs), interference management (IM), and energy harvesting (EH).